Wayang Orang Betawi as a Medium for Cross-Cultural Communication through Local Expression in the Play Udel Jadi Raja - Dela Anjelawati; Lely Arrianie; Dwi Kartikawati (Communica : Journal of Communication, 2026)
In the increasingly multicultural landscape of Indonesia, traditional performing arts are not merely forms of entertainment but serve as vital conduits for intercultural communication. Specifically, Wayang Orang Betawi is a traditional performing art that functions not only as entertainment but also as a medium of cultural communication within Jakarta’s multicultural society. The play Udel Jadi Raja represents local cultural expression embedded with moral values, humour and social symbolism. This study examines how Wayang Orang Betawi serves as a medium for cross-cultural meaning exchange through local expression in the play. While previous scholarship has largely focused on the aesthetic preservation or linguistic vitality of Betawi arts, this study establishes novelty by positioning Wayang Orang Betawi as a medium of cross-cultural meaning exchange. Existing literature often overlooks the communicative function of these performances in mediating social conflict within heterogeneous urban settings. Consequently, the role of traditional humour and symbolism as mechanisms for social cohesion remains underexplored. Specifically, this study analyses how contextual humour functions as intercultural competence and how leadership symbolism conveys egalitarian values to diverse audiences. This study employed a qualitative approach using performance observation, documentation studies and descriptive analysis. Data were analysed by interpreting narrative elements, dialogues, cultural symbols and communication styles presented in Wayang Orang Betawi though the play Udel Jadi Raja. The finding indicate that Udel Jadi Raja facilitates cross-cultural meaning exchange by using Betawi language, distinctive humour and local cultural symbols. The transformation of the character Udel reflects universal values such as honesty, justice, equality and ethical leadership that easy to understand from audiences in diverse cultural backgrounds. Wayang Orang Betawi in Udel Jadi Raja functions as an educational and reflective medium that bridges cultural differences. This performance contributes to strengthening local cultural identity while conveying universal values within a multicultural social context.